Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2141.2011.08852.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Insights in the Pathogenesis and Therapy of Cutaneous T‐cell lymphoma (Mycosis Fungoides and Sezary Syndrome)

Abstract: Cutaneous T-cell lymphomas (CTCL) are a heterogeneous group of malignancies derived from skin-homing T cells. The most common forms of CTCL are Mycosis Fungoides (MF) and Sezary Syndrome (SS). Accurate diagnosis remains a challenge due to the heterogeneity of presentation and the lack of highly characteristic immunophenotypical and genetic markers. Over the past decade molecular studies have improved our understanding of the biology of CTCL. The identification of gene expression differences between normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 190 publications
(177 reference statements)
4
110
1
6
Order By: Relevance
“…[10][11][12] Early stages of CTCL are treated with combinations of UV and immunotherapy, with mono-or polychemotherapy being reserved for cases that do not respond to previous treatment. New therapies based on monoclonal antibodies (including CD25, CD4, CD30, CD3, and CCR4) are being explored, as are other therapeutic agents directed against epigenetic targets (eg, histone deacetylases inhibitors) or proteasome inhibitors such as bortezomib (for a review, see Wong et al 13 ), but to date, aggressive forms of CTCL, including SS and tumoral MF, lack effective targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Early stages of CTCL are treated with combinations of UV and immunotherapy, with mono-or polychemotherapy being reserved for cases that do not respond to previous treatment. New therapies based on monoclonal antibodies (including CD25, CD4, CD30, CD3, and CCR4) are being explored, as are other therapeutic agents directed against epigenetic targets (eg, histone deacetylases inhibitors) or proteasome inhibitors such as bortezomib (for a review, see Wong et al 13 ), but to date, aggressive forms of CTCL, including SS and tumoral MF, lack effective targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main subtypes of CTCL: an indolent form termed mycosis fungoides (MF), which is largely limited to the skin, and Sézary syndrome (SS), an aggressive leukemic variant of the disease which can manifest systemically. [1][2][3] Previous studies have demonstrated defects in cell-mediated immunity in CTCL patients, including altered cytokine profiles and impaired neutrophil function, which lead to a high incidence of recurrent bacterial and viral infections as a result of decreased Th1-mediated immunity. [4][5][6][7][8][9] It has also been reported that natural killer (NK)-cell function is decreased in CTCL patients, [10][11][12][13][14] which could contribute to an overall decrease in the innate immune response to both neoplastic cells and viral or bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Mycosis fungoides and S ezary syndrome are two common CTCL forms, accounting for approximately 67% of cases. For the United States, their incidence has been estimated to be approximately 3 to 8 cases per million inhabitants per year (1)(2)(3). Affected individuals are mostly older than 50 years.…”
Section: Introductionmentioning
confidence: 99%